Evaluating Ideal Capital Structure through WACC And ROA Analysis: Research on IDX-Listed Indonesian Drug Retailers and Distributors (2019-2023) - Reza, Naomi; Heikal, Jerry (International Journal of Scientific Research and Management (IJSRM), 2024)
This study conducts a thorough investigation into the ideal capital structure for companies operating within the drug retail and distribution sub-sector in Indonesia, specifically targeting those that are listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The research compares the Weighted Average Cost of Capital (WACC) with the Return on Assets (ROA) as the value of the firm. The primary objective is to identify the most efficient blend of debt and equity financing that can minimize capital costs while maximizing firm value. The findings reveal that only one company out of the sample has achieved an optimal capital structure, whereas the other two companies have not. For this particular sub-sector, the optimal capital structure is characterized by having more than 68% equity and 0% debt. This paper provides critical insights into strategic financial management and sustainability for companies within this evolving industry. It offers substantial academic contributions and practical guidance that can inform financial decision-making processes within the context of the Indonesian pharmaceutical market. By highlighting these optimal structures, the study aims to guide companies in achieving better financial health and enhancing their competitive edge in the market.